Left atrioventricular coupling index in hypertrophic cardiomyopathy and risk of new-onset atrial fibrillation - Meucci Maria Chiara; Fortuni Federico; Galloo Xavier; Bootsma Marianne; Crea Filippo; Bax Jeroen J; Marsan Nina Ajmone; Delgado Victoria (Elsevier Ireland Ltd, 2025)
Backgrounds
This study aimed to investigate the association between left atrioventricular coupling index (LACI) and the occurrence of atrial fibrillation (AF) in patients with hypertrophic cardiomyopathy (HCM).
Methods
A total of 373 patients with HCM and no history of AF were evaluated by transthoracic echocardiography. LACI was defined by the ratio of left atrial (LA) end-diastolic volume divided by left ventricular (LV) end-diastolic volume. The cut-off value for LACI (≥40%) to identify LA-LV uncoupling was chosen based on the risk excess of new-onset AF described with a spline curve analysis.
Results
The median LACI was 37.5% (IQR: 24.4–56.7) and LA-LV uncoupling (LACI ≥40%) was observed in 171 (45.8%) patients. During a median follow-up of 11 (IQR 7–15) years, 118 (31.6%) subjects developed new-onset AF. The cumulative event-free survival at 10 years was 53% for patients with LA-LV uncoupling versus 94% for patients without LA-LV uncoupling (p < 0.001). Multivariable Cox regression analyses performed separately for each LA parameter showed an independent association between new-onset AF and LACI (hazard ratio [HR], 1.021; 95% CI, 1.017–1.026), LA maximum volume indexed (HR, 1.028; 95% CI, 1.017–1.039), LA minimum volume indexed (HR, 1.047; 95% CI, 1.037–1.060) and LA emptying fraction (HR, 0.967; 95% CI, 0.959–0.977, all p < 0.001). The inclusion of LACI in the multivariate model provided a larger improvement in the risk stratification for new-onset AF, as compared to conventional LA parameters.
Conclusion
In patients with HCM, LACI was more predictive of the occurrence of new-onset AF than conventional LA parameters.